AN EVALUATION OF LEGAL POLICY RELATED TO THE IMPLEMENTATION OF THE SIMULTANEOUS LOCAL ELECTION (FIRST PERIOD OF THE SIMULTANEOUS LOCAL ELECTION) - Riwanto, Agus (Yustisia, 2016)
Indonesia legal policy of the simultaneous local election to appoint a district head had been amended by Law Number 8 of 2015 concerning the local election (governors, regents and mayors) from the regular models to the simultaneous models. Simultaneous local election will be implemented in periods, namely a first period in 2015, a second period in 2017, a third and fourth period will be approximately held from 2018 to the 2021, and a national simultaneous local elections will be held in 2027. The simultaneous local election is aimed to make the efficiency and effectiveness of the budget, time and labor organizer; to eliminate boredom voters; to increase public control. Law Number 8 of 2015 had been reviewed judicially thirdty first times. The Constitutional Court also issued a surpprised decision which change a political constellation of Indonesia. The political aspect of simultaneous  local election in 2015 need to be fixed through the revision of Law Number 8  of 2015 in order to create the system of the simultaneous elections fairly and democratically for the implementation of the next period: the required transfer of election financing from the budget to the state budget; the need to create a model for the preliminary election; restrictions on candidacy requirements; a dispute settlement of the simultaneous local election to the supreme court; a time restrictions on the election administration disputes lawsuit in the Administrative Court; and we need to build a model of election law enforcement system integration.